Qualitative urban analysis an international perspective - Thompson, Susan, 1954-; Tonts, Matthew (Studies in qualitative methodology ;, 2008)
Urban environments in the 21st Century are faced with unprecedented challenges. Globalisation, terrorism/securitisation, fundamentalism/Islamaphobia, demographic shifts and environmental damage all pose profound threats to the urban condition and experience. These meta-challenges invariably raise serious dilemmas for policy makers and practitioners who must increasingly look to researchers for answers to these complex, and at times, overwhelmingly perplexing questions. This book provides a way forward by advocating a 'pragmatic renaissance' within qualitative research - a systematic approach to conducting qualitative research and representing the findings. The editors argue that this approach is essential if we are to develop nuanced and deep levels of understanding of the impacts of these challenges to contemporary urban life. This systematic approach is reflected throughout the book which is divided into two sections - Part One: On Theory and Method; and Part Two: Understanding Key Urban Issues. Individual chapters showcase the utility of qualitative research by providing theoretical, methodological and empirical insights into real life research. Authors draw on research conducted in Australia, England, Ireland, New Zealand, and Sri Lanka and consider issues relating to: the use of social constructionism to understand policy processes and actors; issues and dilemmas in conducting fieldwork, the need for more longitudinal qualitative research; the comparative advantage of qualitative methods in urban policy evaluations; understanding the immigrant settlement experience; dealing with sex workers; ageing in place; and doing action research with Australian Aboriginals. This book will be of interest and use to a wide range of researchers and students in urban planning, housing studies, urban sociology, urban geography, anthropology and community development. In addition, given the applied dimension of the volume, it will have appeal for urban policy makers at the local and strategic level.